Antimicrobial Effectiveness of Clove Oil in Decontamination of Ready-to-Eat Spinach (Spinacia oleracea L.) - Abigail A. Armah; Kelvin F. Ofori; Kenisha Sutherland; Emmanuel Otchere; Winter A. Lewis; Wilbert Long (Foods)
Due to an increased demand for natural food additives, clove oil was assessed as a natural alternative to chemical disinfectants in produce washing. This study assessed the antimicrobial activity of 5 and 10% (v/v) clove oil-amended wash liquid (CO) using a zone of inhibition (ZIB) test and determined the time required to completely inactivate pathogenic bacteria using bacterial death curve analysis. A washing experiment was used to evaluate CO’s ability to inhibit bacterial growth on inoculated RTE spinach and in the wash water. The findings showed that Shigella flexneri, Salmonella Typhimurium, and Salmonella enterica recovery were completely inhibited within 5 min. Escherichia coli and Staphylococcus aureus recovery were completely inhibited at 10 and 30 min, respectively. The ZIB test showed that 5% CO had the highest inhibitory effect on both Salmonella strains and E. coli with approximately 10 mm ZIB diameter. Additionally, 5% CO completely inactivated all bacterial strains on spinach samples and in the wash water except for S. aureus. A total of 80 mg/L peracetic acid (PAA) resulted in >2log CFU/mL recovery on experimental washed samples. These findings suggest that 5% CO was highly effective in inhibiting microbial growth on RTE spinach, potentially contributing to sustainable food safety and shelf-life extension strategies.